The Holy Spirit and Ch'i (Qi) a chiological approach to pneumatology - Yun, Koo Dong (Princeton theological monograph series, 2012)
This book articulates a contextual pneumatology from a perspective of the Eastern idea of ch'i (ki in Korean). Rather than understanding the Spirit from a Westernized philosophical perspective, this book utilizes East Asian categories rooted in the I Ching and Asian religions in dialogue with such prominent Western theologians as Barth, Pannenberg, Moltmann and Harvey Cox. The result is an exciting interaction between the Bible, traditions of the West, and experiences of the Spirit rooted in East Asia. Yun argues that the formal dimension of the Spirit (sangjeok) is present and active in all cultures and religions while the material dimension of the Spirit (muljeok) is categorically revealed and embodied through the life of Jesus Christ, the event of Pentecost, and Charisms given to the church. In making his case, he mediates a creative balance between countercultural and exclusivist models on the one hand, and pluralistic and anthropocentric models on the other.